Pre-optimized phage therapy on secondary Acinetobacter baumannii infection in four critical COVID-19 patients - Nannan Wu; Jia Dai; Mingquan Guo; Jianhui Li; Xin Zhou; Feng Li; Yuan Gao; Hongping Qu; Hongzhou Lu; Jing Jin; Tao Li; Lei Shi; et al. (Emerging Microbes and Infections)
Phage therapy is recognized as a promising alternative to antibiotics in treating pulmonary bacterial infections, however, its use has not been reported for treating secondary bacterial infections during virus pandemics such as coronavirus disease 2019 (COVID-19). We enrolled 4 patients hospitalized with critical COVID-19 and pulmonary carbapenem-resistant Acinetobacter baumannii (CRAB) infections to compassionate phage therapy (at 2 successive doses of 109 plaque-forming unit phages). All patients in our COVID-19-specific intensive care unit (ICU) with CRAB positive in bronchoalveolar lavage fluid or sputum samples were eligible for study inclusion if antibiotic treatment failed to eradicate their CRAB infections. While phage susceptibility testing revealed an identical profile of CRAB strains from these patients, treatment with a pre-optimized 2-phage cocktail was associated with reduced CRAB burdens. Our results suggest the potential of phages on rapid responses to secondary CRAB outbreak in COVID-19 patients.